Best Buy : creating a winning customer experience in consumer electronics - Sawhney, Mohanbir S.; Goodman, Pallavi; Keerthivasan, Ganesan (London : Kellogg School of Management, 2017)
After a successful run for many years as a resilient consumer electronics giant, Best Buy was under intense pressure at the end of 2014. Even as competitors like Circuit City melted away, Best Buy had been able to withstand the onslaught of online behemoth Amazon and discount retailers like Target and Walmart. However, its competitive position was threatened as online shopping became more popular, particularly among millennial customers. With a new leadership team, Best Buy had recently undertaken bold initiatives to expand and refine its online presence and position itself for success. These initiatives had produced encouraging results, but Best Buy needed to do more to stem the loss of market share to Amazon and to become more relevant to millennial customers. To address these challenges, Best Buy approached the Kellogg School of Management to solicit ideas from student teams by sponsoring a Business Challenge competition. The teams came up with several strategic initiatives. Best Buy needed to evaluate these initiatives on two criteria: First, how well did these initiatives leverage Best Buy's privileged physical assets (stores, salespeople, and Geek Squad services staff) to create a winning customer experience? Second, how effective would these initiatives be in attracting and retaining millennial customers?
Originally Published InSawhney, M., Goodman, P., & Keerthivasan, G. (2017). Best Buy: Creating a winning customer experience in consumer electronics. 5-217-251. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Best Buy (Firm) -- Management; Circuit City Stores; Amazon.com (Firm); Target Corporation; Wal-Mart (Firm); Organizational change -- Case studies; Electronic commerce -- Case studies; Household electronics industry -- Marketing -- Case studies